1997
DOI: 10.1007/s003810050111
|View full text |Cite
|
Sign up to set email alerts
|

Huge ossified crust-like subdural hematoma covering the hemisphere and causing acute signs of increased intracranial pressure

Abstract: We report the successful removal of an ossified crust-like chronic subdural hematoma (SDH) covering the hemisphere in a 16-year-old boy. In this article, the importance of the surgical approach is stressed, and the rarity of this condition in the neurosurgical literature is also outlined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 9 publications
1
24
0
1
Order By: Relevance
“…The exact incidence of calcification is not known, though in 1973, Harwood-Nash [8]reported a 10% incidence in the chronic subdural hematoma detected by skull film in children. Calcification and ossification in chronic subdural hematoma have long been reported [1, 3, 9], and severe forms of calcification in the subdural hematoma have been reported as ossified chronic subdural hematoma [6, 9, 10]. It has also been reported in subdural empyema [11, 12].…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The exact incidence of calcification is not known, though in 1973, Harwood-Nash [8]reported a 10% incidence in the chronic subdural hematoma detected by skull film in children. Calcification and ossification in chronic subdural hematoma have long been reported [1, 3, 9], and severe forms of calcification in the subdural hematoma have been reported as ossified chronic subdural hematoma [6, 9, 10]. It has also been reported in subdural empyema [11, 12].…”
Section: Discussionmentioning
confidence: 91%
“…Clinical presentation of calcified subdural hematoma varies widely, from asymptomatic [13, 14, 25, 26]in some to acute raised intracranial pressure in others [6, 13]. Ide et al [14]in 1993, reported 3 cases in whom the calcified chronic subdural hematoma was without symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the interval between the initial hemorrhage and the development of calcification is generally a long-time course, varying between 6 months and many years. 1,10,19 The course of the disease was an average of 12.7 years in the 37 published cases. Third, calcification of CSDH is of various etiologies; it was observed in 46 cases in which trauma was the most common incentive for CCDSH in older patients, whereas shunting is common in the young.…”
Section: Clinical Characteristicsmentioning
confidence: 98%